PENGEMBANGAN KARAKTER RELIGIUS OLEH GURU PADA ANAK USIA 5-6 TAHUN MELALUI PEMBIASAAN DI PAUD CERIA KUBU RAYA - Olifia Widyanti; Marwawi R; Dian Miranda (Universitas Tanjungpura, 2022)
AbstractThis study aims to describe the development of religious character by teachers in children aged 5-6 years through habituation in PAUD Ceria Kubu Raya. The research method is a descriptive method with a qualitative research form. The research subjects were teachers in group A, children aged 5-6 years at PAUD Ceria Kubu Raya. The research location for Ceria Kubu Raya PAUD. Data collection techniques in research are observation, interviews, and documentation. The results of the study that; 1. Planning for the development of religious character by teachers for children aged 5-6 years through habituation is to formulate goals and formulate standard operating procedures adapted to the indicators of achievement of children's development 2. Steps of habituation in developing the religious character of teachers have been carried out in accordance with the following steps: the steps listed in the SOP, 3. Evaluation of the development of the religious character of the teacher making an assessment when the activity process takes place where the teacher observes each other's activities, 4. The obstacles faced by the teacher in developing the religious character of the child are from the child's family factor, 5. The efforts made by the teacher to overcome these obstacles is to always remind and motivate children.Keywords: Development, Religious Character And Habituation